Characterization of Multi Pixel Photon Counters for T2K Near Detector - Retiere, F; Du, Y; Foreman, S; Kitching, P; Kostin, A; Lindner, T; Low, M; Masliah, P; Moult, I; Oser, S; Tanaka, H; Vacheret, A (2009)
The T2K Near Detector (ND280) will be equipped with about 50,000 Pixel Photon Counters (MPPCs). Because it is the first time that these devices are being used in such a large quantity in a physics experiment, MPPCs have not been characterized in detail yet. These proceedings focus on investigating the MPPC response to low light level by characterizing quantitatively all the relevant phenomena, especially cross-talk and after-pulsing. Monte Carlo simulations of the MPPC response including all the relevant phenomena agree well with the data. Crown Copyright © 2009.